2014
DOI: 10.1088/0004-637x/788/1/10
|View full text |Cite
|
Sign up to set email alerts
|

The Fast Uv Variability of the Active Galactic Nucleus in Fairall 9

Abstract: We present the results from a new optical/UV/X-ray monitoring campaign of the luminous Seyfert galaxy Fairall 9 using the Swift satellite. Using the UV-Optical Telescope on Swift, we find correlated optical/UV variability on all timescales ranging from the sampling time (4 days) to the length of the campaign (2.5 months). In one noteworthy event, the UW2-band flux dips by 20% in four days, and then recovers equally quickly; this event is not seen in either the optical or the X-ray bands. We argue that this eve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…A possible solution includes contribution from both components, a thermal corona as well as a synchrotron jet (Soldi et al 2014). Such a combined model has been proposed for other radio galaxies as well, such as 3C120 (Lohfink et al 2014) and 3C273 (Grandi & Palumbo 2004;Madsen et al 2015a). However, as Rothschild et al (2006) and later Burke et al (2014) found, the X-ray continuum shape is remarkably stable over time, despite significant flux changes.…”
Section: The Geometry and Physics Of The X-ray Coronamentioning
confidence: 99%
“…A possible solution includes contribution from both components, a thermal corona as well as a synchrotron jet (Soldi et al 2014). Such a combined model has been proposed for other radio galaxies as well, such as 3C120 (Lohfink et al 2014) and 3C273 (Grandi & Palumbo 2004;Madsen et al 2015a). However, as Rothschild et al (2006) and later Burke et al (2014) found, the X-ray continuum shape is remarkably stable over time, despite significant flux changes.…”
Section: The Geometry and Physics Of The X-ray Coronamentioning
confidence: 99%
“…Other than reddening, we also need to account for the host galaxy flux contribution to each of the filter band fluxes. We follow the procedure used in Lohfink et al (2014). Because the UVOT images are insufficient to perform a decomposition of the AGN and host galaxy contributions, we use the results from HST imaging as a basis.…”
Section: Swiftmentioning
confidence: 99%
“…Fairall 9 has also been observed in a number of multi-wavelength campaigns to probe the central engine including the broad line region (Chapman et al 1985;Wamsteker et al 1985;Morini et al 1986;Koratkar & Gaskell 1989;Recondo-Gonzalez et al 1997;Zheng et al 1995;Lohfink et al 2012bLohfink et al , 2014. Some of the campaigns cover only UV (Chapman et al 1985;Rodríguez-Pascual et al 1997;Koratkar & Gaskell 1989) or UV and optical (Wamsteker et al 1985;Lub & de Ruiter 1992;Santos-Lleó et al 1997) or UV and X-rays (Zheng et al 1995;Morini et al 1986) to search for possible correlation between continua at different wavelengths, and between the continuum and broad emission lines.…”
mentioning
confidence: 99%
“…; Lohfink et al 2014). Lohfink et al (2014) studied nearly a 2.5-months of data from a Swift monitoring campaign which revealed the UV signature of X-ray flares.…”
mentioning
confidence: 99%
See 1 more Smart Citation